2017
DOI: 10.1007/s11187-017-9935-x
|View full text |Cite
|
Sign up to set email alerts
|

Green entrepreneurship in the sharing economy: utilising multiplicity of institutional logics

Abstract: The green potential of the sharing economy to exploit underutilised or redundant resources has generated a considerable interest and expectations on the part of government institutions, investors and consumers. Alongside the emerging green logic, more established economic and social logics appear to be critical for growth of sharing platforms. Applying an institutional logics approach, this paper investigates how entrepreneurial teams in the sharing economy deal with this complexity of expectations of various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 51 publications
2
62
0
3
Order By: Relevance
“…However, it is easy to imagine alternative explanations as well. For example, it has been suggested that many sharing economy platforms emphasize environmental and communal values to convince regulators of their positive societal effects [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is easy to imagine alternative explanations as well. For example, it has been suggested that many sharing economy platforms emphasize environmental and communal values to convince regulators of their positive societal effects [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…Such initiatives are stressing the promises and positive effects of sharing for the society and the environment [96]. However, prominently claiming the promising green and social logics may cause consumers to become especially aware of the potential and actual detrimental external effects of sharing businesses [97][98][99]. This may, for example, include considerations about consumptive rebound effects [62], legal and regulatory concerns [74], the economization of formerly non-economic domains [7,39], aggravation local housing markets [100], discrimination [76,77], or the creating of a gig/sharing precariat [39].…”
Section: The Mediating Role Of Perceived Risk Of Sharing (H3)mentioning
confidence: 99%
“…Vadim et al [33] The authors analyse the potential of sharing economies, how they can be used to explore different kinds of resources and how entrepreneurial teams deal with the expectations and complexity of different institutions.…”
Section: Study Description Yearmentioning
confidence: 99%
“…In Reference [33], the authors discuss the green logic and environmental benefits and unknown downsides of a shared economy. The authors mentioned the different schemes used to define a shared-economy and which actors are involved in the said economy, with the most common ones being the Peer-to-Peer (P2P) that occupy 3 4 of the defined models.…”
Section: Web Platformmentioning
confidence: 99%